Antagonistic potential of selected fungal and bacterial biocontrol agents against Colletotrichum truncatum of soybean seeds - Begum, Most Mahbuba; Meon, Sariah; Mior Ahmad, Zainal Abidin; Puteh, Adam; A. Rahman, Mahfar (Universiti Putra Malaysia Press, 2008)
Ten fungal and bacterial biocontrol agents (BCAs) were evaluated in vitro for their antagonistic potential against Colletotrichum truncatum isolated from soybean seeds. Two fungal BCAs namely Trichoderma virens isolate UPM23 and Trichoderma harzianum isolate UPM40 and a bacterial BCA namely Pseudomonas aeruginosa isolate UPM13B8 strongly inhibited the growth of C. truncatum based on high PIRG values in dual culture and culture filtrate tests. Studies on the mechanism of action using mycoparasitism technique and antibiosis observed under light microscope revealed that T. virens and T. harzianum inhibited the growth of C. truncatum by coiling and penetration into the hyphae. Consequently, the hyphae of C. truncatum became malformed and swollen. Pseudomonas aeruginosa also caused mycelial malformation; the mycelia turned vacuoled and swollen in or at tips of hyphae. Pseudomonas aeruginosa gave the highest PIRG value in the culture filtrate test, suggesting that antibiosis could be the main mechanism of antagonism. No inhibitory effect was observed on soybean seeds and seedlings when the seeds were artificially inoculated with T. virens, T. harzianum and P. aeruginosa. On the contrary, T. virens and T. harzianum were found to enhance seed germination and seedling establishment, while P. aeruginosa enhanced fresh and dry weights of seedlings.